Lim Guan Eng dari penjara ke tampuk kuasa - Wan Hamidi Hamid; Faisal Mustaffa (Research for Social Advancement, 2009)
On Lim Guan Eng, Chief Minister of the State of Penang and Secretary-General of the Malaysian Democratic Action Party